Design and build an inverting switching regulator - Foo, Fang Ren (2017)
For this project, the objective is to design and build a switching inverting regulator, using MC 34063A microchip. With further advances in technology, the demand for power is increasing. A significant portion of the demand comes from electronic devices, which requires specific input parameters to operate properly. Therefore, there is a need for properly designed regulators. The MC 34063A integrated circuit (IC) is a very versatile specimen, therefore it is being widely used. Depending on the different applications, with an external circuit connection, the MC 34063A can become a boost (step-up), buck (step-down) or buck-boost (inverting) regulator. The desired output is a -12V DC current which can supply a 200mA load with a 5V ± 5% input voltage. Results of the experiments were recorded, analysed and compared with theoretical predictions. Different input values are also tested to examine the effect of the loads on the switching inverting regulator. With the help from this report and other similar reports, the three regulator configurations can be designed and built onto a single board which can be toggled by adjusting a switch. The efficiency of the regulator can also be further improved.